Subcutaneous therapy in palliative care - Marques, Cátia (2005)
Introduction: Regardless of its importance, need and efficacy in specific situations, namely in continued and palliative care, the subcutaneous route (SR) is still scarcely applied in Portugal. SR is useful to administer drugs and fluids (hypodermoclysis). Knowing its main characteristics and relevance is essential for Family Doctors, in order to assume their responsibility in taking care of patients until the moment of their death. Objective: To determine the utilisation rate of SR in palliative care; to describe diseases, indications, drugs administered and complications associated with the use of SR. Type of study: descriptive, cross-sectional. Population and Setting: Patients receiving palliative care in June, 2004, in the Continued Care Unit of Odivelas Health Center, Portugal. Methods: The authors reviewed the medical records of the 348 patients included in the study about gender, age, the use of SR, its indications, drugs used, mode of administration and complications associated. Results: About 3.5% of patients received subcutaneous therapy. The main diagnoses in this group were cancer (41,67%) and stroke (41,67%); the major indication to the use of SR was agony (50%). Hypodermoclysis was used in 41,67%, and exclusive administration of drugs in 58,33% of the SR group patients; butilscopolamin was the most used drug (66,67%). In all the cases drugs were administered in bolus and hypodermoclysis as a continuous infusion. No complications of the use of SR were reported. Conclusions: The use of SR in palliative care is low, with a dimension still incompatible with its benefits.